Molecular Perspectives on Prostate Cancer: The Role of microRNAs in Androgen Receptor Regulation - Asbiel Felipe Garibaldi-Ríos; Alicia Rivera-Cameras; Luis E. Figuera; Guillermo Moisés Zúñiga-González; Belinda Claudia Gómez-Meda; José Elías García-Ortíz; Martha Patricia Gallegos-Arreola (Receptors)
Prostate cancer (PCa) is the most prevalent cancer among men globally. In addition to environmental risk factors, genetic factors play a crucial role in its development and progression, highlighting the regulation of key genes as an essential aspect. The androgen receptor gene (AR) plays a pivotal role in this disease, so its post-transcriptional regulation must be meticulously coordinated. In this review, we explore the role of microRNAs (miRNAs) in the regulation of AR in PCa, a field not yet fully investigated. We note that the AR, due to its extensive 3′UTR region, is targeted by numerous miRNAs, and that this regulation can occur at different levels: directly, indirectly, and through mutual regulation, thus amplifying the influence of these molecules on AR regulation.